2022
DOI: 10.3389/fonc.2022.914192
|View full text |Cite
|
Sign up to set email alerts
|

A Practical Nomogram and Risk Stratification System Predicting the Cancer-Specific Survival for Patients With Advanced Hepatocellular Carcinoma

Abstract: BackgroundHepatocellular carcinoma (HCC) has the highest cancer-related mortality rate. This study aims to create a nomogram to predict the cancer-specific survival (CSS) in patients with advanced hepatocellular carcinoma.MethodsPatients diagnosed with advanced HCC (AJCC stage III and IV) during 1975 to 2018 were obtained from the Surveillance, Epidemiology, and End Results (SEER) database. Qualified patents were randomized into training cohort and validation cohort at a ratio of 7:3. The results of univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…[26,27] A number of previous studies have shown that age, gender and marital status are all prognostic factors affecting survival in patients with hepatocellular carcinoma. [28][29][30] In our study model, however, these factors were not associated with early death in patients with metastatic HCC.…”
Section: Discussioncontrasting
confidence: 64%
“…[26,27] A number of previous studies have shown that age, gender and marital status are all prognostic factors affecting survival in patients with hepatocellular carcinoma. [28][29][30] In our study model, however, these factors were not associated with early death in patients with metastatic HCC.…”
Section: Discussioncontrasting
confidence: 64%
“…We used univariate and multivariate Cox regression analyses to evaluate the independent prognostic value of the risk score. In the training set, a nomogram was developed based on independent risk factors, and risk scores were calculated for each patient [ 18 , 19 ]. Training and validation sets were used to estimate the accuracy of the nomogram model.…”
Section: Methodsmentioning
confidence: 99%